Gender Differences in Executive Functions of Patients Operated for Mild to Moderate Epidural Hematoma - Singh, Shweta; Sarraf, Seema Rani; Tripathi, Adarsh; Ojha, Bal Krishna; Singh, Amandeep (Indian Journal of Neurosurgery, 2022)
Background Impairment in neurocognitive functions are commonly followed by Epidural hematoma (EDH) . This cross-sectional study was aimed to study gender differences in neurocognitive functions in mild to moderate epidural hematoma patients (43 male and 19 female patients) post-surgery using standardized assessment tools of comprehensive neurocognitive function attention, speed, working memory, fluency, set-shifting, perseveration, planning and response inhibition.Methods Descriptive statistics, i.e., mean and standard deviation (SD) values were computed, and a t-test was applied for further exploration.Results The analysis of results shows that on the test of working memory, female group scored better as significant differences were found on N-Back (2 Back versions) and digit span-backward. On the verbal fluency test (COWA), significant difference was found as females scored higher than the male group on total responses. However, the male group was higher in total time and error than the female group on the test of sustained attention and divided attention.Conclusion This study shows interesting results in terms of gender differences in executive function of patients operated for mild to moderate epidural hematoma. These findings have significant clinical and implications for planning intervention. The neuropsychological rehabilitation of patients operated for mild to moderate epidural hematoma has a crucial role in enhancing their recovery and overall functioning. Inputs about gender differences in neuro psychological functioning of these patients would help in decision making regarding neuropsychological rehabilitation incorporating the gender related differences too in their intervention plan.
Keywords: traumatic brain injury; epidural hematoma; neurocognitive functions; executive functions